2014
DOI: 10.1021/nn502690b
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Integrin Ligand Patterns Determine Melanoma Cell Behavior

Abstract: Cells use integrin receptors to adhere onto surfaces by binding to ligands such as the arginine-glycine-aspartic acid (RGD) motif. Cancer cells make use of this adhesion process, which has motivated the development of integrin-directed drugs. However, those drugs may exert paradoxical effects on tumor progression, which raises the question of how integrin function is governed in tumor cells on the nanoscale. We have utilized precisely defined and tunable RGD ligand site densities spanning 1 order of magnitude,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 60 publications
6
51
0
Order By: Relevance
“…The MC model simulation results showed that integrin clustering decreased when the ligand spacing was larger than some threshold (~60nm), in good agreement with previous experimental results, which found that cell adhesion formed only if the ligand spacing was less than a particular threshold such as ~60nm [19][20][21][22][23][24][25]. As a matter of fact, the increase in the ligand spacing directly decreased the chance of active integrins during diffusion to bind to the underlying ligands and thus reduced the probability of integrin clustering.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The MC model simulation results showed that integrin clustering decreased when the ligand spacing was larger than some threshold (~60nm), in good agreement with previous experimental results, which found that cell adhesion formed only if the ligand spacing was less than a particular threshold such as ~60nm [19][20][21][22][23][24][25]. As a matter of fact, the increase in the ligand spacing directly decreased the chance of active integrins during diffusion to bind to the underlying ligands and thus reduced the probability of integrin clustering.…”
Section: Discussionsupporting
confidence: 88%
“…Likewise, it has been experimentally revealed that the spacing of integrin ligands on two-dimensional flat matrices/substrates can essentially exert a strong impact on the formation and development of nascent adhesions that are the precursors of FAs [1,13]. Only on the premise that the underlying ligand spacing is smaller than some specific threshold such as ~60nm for rigid substrates in some experiments, cells begin to adhere and spread [16][17][18] with enhancement of initial adhesion strength [19][20][21][22], which is accompanied by an increase in integrin cluster size and density [23], then formation of stable FAs and actin cytoskeletons [24], and finally activation of cellular functions and signaling events [25]. Otherwise, it seems impossible for cells to cause integrin clustering and the occurrence of nascent FAs [1,13].…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that certain functionalized nanoparticles promoted growth of specific cell lines while inhibiting others, due to the differences of cell sensitivity responding to the environment, which was explained precisely in their article. Another example is the work of Amschler et al (2014). They generated bioinspired surfaces by functionalization of AuNPs (ranging from 30 to 120 nm) with cyclic (RGDfE), a pentapeptide specific for the a V b 3 integrin.…”
Section: Nanoparticle Interfacesmentioning
confidence: 99%
“…[1][2][3][4][5] Among various engineered interfaces, the patterned surfaces in which adhesive islands located on a non-adhesive background have attracted much interest in recent years.…”
Section: Introductionmentioning
confidence: 99%